O servidor público no discurso argumentativo dos jornais O Globo e O Estado de São Paulo nos últimos 30 anos - Vasconcellos, Bruna Homrich (2020)
The concern that moves us in this research is to understand how journalism has been building, in the last 30 years, its discourse on public servants. Our general objective is to analyze the argumentative strategies used in the speeches of the newspapers O Globo and O Estado de São Paulo to elaborate a narrative about public servants. We understand journalism as a social actor that takes part in the argumentative process, because, by suggesting snapshots of reality and covering them with meanings, it not only presents us with a view of things, but calls us to share its view. Every enunciation carries with it an intentionality and, consequently, lists certain strategies in order to satisfy it. We maintain the hypothesis that by using argumentative strategies, journalism not only constructs a stereotyped narrative about the public servant, but also presents its perception of a minimal state and of a neoliberal cut. The articles selected to compose our research corpus were submitted to an analysis protocol anchored in strategies proposed by Amossy (2016) and Charaudeau (2015b; 2016). From the application of the protocol, it was possible to apprehend the preponderance of some argumentative strategies, a stereotyped narrative pattern about public servants and an increasing alignment of the journalistic discourse with the political discourse on matters concerning the civil service.